RECEPCIÓN Y TRADUCCIÓN DE LA NARRATIVA BREVE FRANCESA DEL XIX POR LOS MODERNISTAS ESPAÑOLES: UN CASO PROVINCIANO - Saura Sánchez, Alfonso (Anales de Filología Francesa, 2007)
In 1907 a new literary journal was launched in the Mediterranean town of Cartagena, which, at the turn of the century, had already become highly dynamic in socio-economic terms. The journal was actually promoted by a group of young literary persons who, following Unamuno’s directions, had an interest in modernism. The project, which lasted for eight months, was led by Vicente Medina, a local poet with good connections in the literary world. In these eight months 16 short stories by 19th and early 20th century French authors were published, among other texts. Some of them were signed by highly reputed writers, like Gautier, Dumas Jr, Maupassant. The majority, however, belonged to Parisian writers à la mode at the turn of the century: Bonnetain, Coppée, Hugues Le Roux, Metenier, Prevost, Richepain and Silvestre. A third group comprised new authors who started there literary careers at that time: Mauclair, Colette. An analysis of the translations is also accomplished in this paper.